1999
DOI: 10.1002/(sici)1521-3927(19990501)20:5<245::aid-marc245>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of MgCl2-supported Ziegler catalysts by high resolution transmission electron microscopy

Abstract: SUMMARY: The surface atomic structure of MgCl 2 crystalline particles and MgCl 2 -supported Ziegler catalysts was observed by means of high resolution transmission electron microscopy.Step-terrace surface structures, characteristic of the structure of the MgCl 2 crystal, are found in the observed images of MgCl 2 particles. The observation of the structure of MgCl 2 -supported Ziegler catalysts shows that the MgCl 2 crystals are severely deformed by the processes of catalyst preparation. Due to the preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 10 publications
(11 reference statements)
1
26
0
Order By: Relevance
“…CLU‐27‐110, in turn, has undergone relaxation not only at lateral terminations, but also in the interior; this resulted into a slight wave‐like deformation of the whole cluster (see arrows in Figure ‐bottom/right, and SI). Similar effects have been reported before in computational as well as experimental studies of ‘activated’ MgCl 2 . For this cluster too, terminal Mg‐Cl bonds at corners are quite short ( r 3 = 2.2 Å in Figure ‐top/right).…”
Section: Results Annd Discussionsupporting
confidence: 89%
“…CLU‐27‐110, in turn, has undergone relaxation not only at lateral terminations, but also in the interior; this resulted into a slight wave‐like deformation of the whole cluster (see arrows in Figure ‐bottom/right, and SI). Similar effects have been reported before in computational as well as experimental studies of ‘activated’ MgCl 2 . For this cluster too, terminal Mg‐Cl bonds at corners are quite short ( r 3 = 2.2 Å in Figure ‐top/right).…”
Section: Results Annd Discussionsupporting
confidence: 89%
“…A study using density functional theory (DFT) calculations showed that MgCl 2 had the (001) and (104) planes at crystallographic equilibrium, but activated MgCl 2 could also have the (110) plane if internal donors or TiCl 4 were present . Mori et al observed with high‐resolution transmission electron microscopy, that lateral planes of mechanically activated MgCl 2 were predominantly composed of the (110) and (104) planes. Andoni et al reported preferential growth of MgCl 2 crystal along the (110) direction in the presence of 1,3‐diethers, while the growth occurred along both the (110) and (104) directions in the presence of phthalates.…”
Section: Introductionmentioning
confidence: 99%
“…[339,340] The( 110) surface contains four-coordinate Lewis acidic Mg sites,a nd the (104) surface contains fivecoordinate Mg sites (Figure 3). [339,340] The( 110) surface contains four-coordinate Lewis acidic Mg sites,a nd the (104) surface contains fivecoordinate Mg sites (Figure 3).…”
Section: Characterization Of the Precatalystsmentioning
confidence: 99%